2020
DOI: 10.1002/ar.24508
|View full text |Cite
|
Sign up to set email alerts
|

The third vascular route of the inner ear or the canal of Cotugno: Its topographical anatomy, fetal development, and contribution to ossification of the otic capsule cartilage

Abstract: Three vascular routes to the inner ear are known: (a) through the internal acoustic meatus with the vestibulocochlear nerve; (b) from the endolymphatic duct aperture; and (c) along the canal of Cotugno (CC) inserted into the vestibular part of the ear from the superior or brain side. The third is believed to contain only veins. Examinations of 33 human embryos and fetuses at 6–40 weeks demonstrated that (a) the CC appeared as a recess of epidural mesenchymal tissues at the superior aspect of the otic capsule c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…Later, the active and delayed ossification toward otosclerosis was defined as a sequential process: (a) "osteocyte-mediated absorption" of the (c) proliferation of vessels and production of lamellar bone (reviewed by Merchant & Nadol Jr., 2010). Therefore, the abnormal calcification at the tympanostapedial syndesmosis may be similar to the ossification in and along the subarcuate process, the latter of which was recently described in detail by the present last author (Honkura et al, 2020). The FAF did not contain a woven bone structure in the present specimens.…”
Section: Discussionsupporting
confidence: 79%
“…Later, the active and delayed ossification toward otosclerosis was defined as a sequential process: (a) "osteocyte-mediated absorption" of the (c) proliferation of vessels and production of lamellar bone (reviewed by Merchant & Nadol Jr., 2010). Therefore, the abnormal calcification at the tympanostapedial syndesmosis may be similar to the ossification in and along the subarcuate process, the latter of which was recently described in detail by the present last author (Honkura et al, 2020). The FAF did not contain a woven bone structure in the present specimens.…”
Section: Discussionsupporting
confidence: 79%
“…In this context, a bony AP inserted into the cartilaginous AT corresponded to another type of “mosaic” or complex. Moreover, bones at multiple stages of endochondral ossification coexisted, as seen in the temporal bone petrosal portion of late‐term fetuses (Honkura et al, 2020; Michaels et al, 2010). Finally, we did not find the lingula sphenoidalis although it was considered to ossify at 4 month along the lateral aspect of the internal carotid artery (see also the next subsection).…”
Section: Discussionmentioning
confidence: 99%
“…During this period, human fetuses have a large gap between the cerebrum and the calvaria [ 23 25 ]. In contrast, the cranial base is close to the brainstem, thalamus, and hypothalamus [ 23 25 ]. This study demonstrated the development of a temporary connecting apparatus from 7 to 14 WD.…”
Section: Discussionmentioning
confidence: 99%
“…During the fetal period, the peak increase in brain weight occurs between 9 and 18 weeks [22]. During this period, human fetuses have a large gap between the cerebrum and the calvaria [23][24][25]. In contrast, the cranial base is close to the brainstem, thalamus, and hypothalamus [23][24][25].…”
Section: Plos Onementioning
confidence: 99%